Genomic paleontology provides evidence for two distinct origins of Asian rice (Oryza sativa L.) - Vitte, C.; Ishii, T.; Lamy, F.; Brar, D.; Panaud, O. (Molecular genetics and genomics : MGG, 2004)
The origin of rice domestication has been the subject of debate for several decades. We have compared the transpositional history of 110 LTR retrotransposons in the genomes of two rice varieties, Nipponbare (Japonica type) and 93-11 (Indica type) whose complete sequences have recently been released. Using a genomic paleontology approach, we estimate that these two genomes diverged from one another at least 200,000 years ago, i.e., at a time which is clearly older than the date of domestication of the crop (10,000 years ago, during the late Neolithic). In addition, we complement and confirm this first in silico analysis with a survey of insertion polymorphisms in a wide range of traditional rice varieties of both Indica and Japonica types. These experimental data provide additional evidence for the proposal that Indica and Japonica rice arose from two independent domestication events in Asia.